2017
DOI: 10.1002/2211-5463.12193
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of dimethyl sulfoxide on red blood cells, platelets, and vascular endothelial cells in vitro

Abstract: Dimethyl sulfoxide (DMSO) is widely used in biological studies as a cryoprotective agent for cells and tissues, and also for cryopreserved platelets (PLTs). However, few data on the toxic effects of DMSO following intravenous infusion of cryopreserved PLTs are available. The aim of this study was to explore dose‐related effects of DMSO on red blood cells (RBCs), PLTs and vascular endothelial cells in vitro. The results showed that DMSO treatments had significant effects on RBCs, affecting osmotic fragility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 25 publications
4
53
0
Order By: Relevance
“…For example, in vitro toxicity in a retinal neuronal cell line from rats was observed at DMSO concentration higher than 1% (v/v) (Galvao et al 2013). DMSO was also shown to affect red blood cells, platelets and vascular endothelial cells in vitro at a concentration > 0.6% v/v and bacterial strains, such as S.epidermidis and S.paratyphia at a concentration >5% (v/v) (Yi et al, 2017). Another study revealed that DMSO with 0.5%-2% v/v significantly suppressed the expression of many pro-inflammatory cytokines/chemokines (Proost et al, 2016).…”
Section: Toxicity Assessment Of the Degraded Mc-lr Samplesmentioning
confidence: 99%
“…For example, in vitro toxicity in a retinal neuronal cell line from rats was observed at DMSO concentration higher than 1% (v/v) (Galvao et al 2013). DMSO was also shown to affect red blood cells, platelets and vascular endothelial cells in vitro at a concentration > 0.6% v/v and bacterial strains, such as S.epidermidis and S.paratyphia at a concentration >5% (v/v) (Yi et al, 2017). Another study revealed that DMSO with 0.5%-2% v/v significantly suppressed the expression of many pro-inflammatory cytokines/chemokines (Proost et al, 2016).…”
Section: Toxicity Assessment Of the Degraded Mc-lr Samplesmentioning
confidence: 99%
“…Although DMSO is an efficient solvent for water‐insoluble compounds and has cryoprotectant action, it has recently been concluded that DMSO is toxic to some tissues . In addition, the topical application may cause inflammatory action such as mild local transient burning, rash and pruritus .…”
Section: Discussionmentioning
confidence: 99%
“…This is another fact that would contradict the good results of this compound recently brought forward by several authors [34][35][36][37][38][39] Although DMSO is an efficient solvent for water-insoluble compounds and has cryoprotectant action, it has recently been concluded that DMSO is toxic to some tissues. 44 In addition, the topical application may cause inflammatory action 45 such as mild local transient burning, rash and pruritus. 46 Thus, the tissues around the avulsed tooth were probably more sensitive to the toxic effects of DMSO, which may have affected the viability of the periodontal ligament after avulsion and the prognosis of the replanted tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Dimethyl sulfoxide (DMSO) is widely used as a cryopresevant agent for various types of stem cells and other body tissues [21]. DMSO has the following adverse effects: skin irritation; garlic breath or body odor; abdominal pain, nausea, vomiting and diarrhea; bronchospasm, chest tightness and dyspnea; altered heart rate and blood pressure, arrhythmias, heart block and myocardial ischemia; various degrees of neurotoxicity, renal and hepatic dysfunction and death [20,21]. Also, it has in vitro toxicity in the form of induction of red blood cell hemolysis and reduction in platelet aggregation and activity [21].…”
Section: Discussionmentioning
confidence: 99%